2017
DOI: 10.21767/2171-6625.1000208
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mechanisms of the Prion Protein Gene Mutations: A Review and Speculative Hypotheses for Pathogenic Potential of the Pro39Leu Mutation in the Associated FTD-Like Phenotype

Abstract: Recently, a novel, missense Pro39Leu mutation, to date unique in the N-terminal domain of the prion protein (PrP), has been reported in three patients affected by frontotemporal lobar degeneration (FTLD) syndrome, in the absence of mutations in genes known to cause dementia. Dominantly inherited mutations in the PRNP, the gene encoding PrP, have been associated with neurodegenerative disorders including Creutzfeldt-Jacob disease (CJD), Gerstmann-Sträussler-Scheinker syndrome (GSS), and Fatal Familial Insomnia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The presence of any pathogenic point mutation in residues 23–50 remained unknown until the description of the missense Pro39Leu mutation, reported in two patients affected by FTLD syndrome [13] and successively in another FTD patient [14], in which all three patients were negative for mutations in other known causative genes. Pro39Leu is the first mutation described in the N-terminal domain located in a codon (the 39 codons), before the known 102 residue (pathogenic mutation Pro102Leu causative of GSS) [15]. Nevertheless, functional studies to determine whether and how the Pro39Leu mutation may exert its pathogenic effects still remain to be implemented.…”
Section: The Prnp Gene Mutations and Inherited Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of any pathogenic point mutation in residues 23–50 remained unknown until the description of the missense Pro39Leu mutation, reported in two patients affected by FTLD syndrome [13] and successively in another FTD patient [14], in which all three patients were negative for mutations in other known causative genes. Pro39Leu is the first mutation described in the N-terminal domain located in a codon (the 39 codons), before the known 102 residue (pathogenic mutation Pro102Leu causative of GSS) [15]. Nevertheless, functional studies to determine whether and how the Pro39Leu mutation may exert its pathogenic effects still remain to be implemented.…”
Section: The Prnp Gene Mutations and Inherited Prion Diseasesmentioning
confidence: 99%
“…To date, most of the known PRNP pathogenic mutations have been identified in the C-terminal domain. Recently, a missense P39L mutation in N-terminal domain of the prion protein was reported by several authors, in patients affected by frontotemporal lobar degeneration (FTLD) syndrome, which were negative for mutations in genes causative of dementia [13,14,15]. Given all these data, the purpose of our report is to provide updated insights into the pathogenic mechanisms of PRNP mutations, emphasizing the differences between the C- and N-terminal domains and focusing in particular on the lesser-known flexible N-terminal, for which recent biophysical evidence has revealed a physical interaction with globular C-terminal domains of PrP C [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that P39L may result in less-rigid N-terminus of PrP, and it could permit abnormal cell–protein interactions. 134 136 …”
Section: Summary Of Prion Mutationsmentioning
confidence: 99%
“…The prion agents have been extracted and studied. Prions can be examined in growing yeast cultures, and the propagation of prions can be observed in controlled, experimental settings [24][25][26]. In culture and in ex vivo systems, we can now study how various cellular processes may participate in the conversion of normal prion proteins into infectious prion agents [26,27].…”
Section: Section 82 Prion Diseases: Fulfilling Koch's Postulates Bumentioning
confidence: 99%